IoT Frequency Band Channelization in Indonesia as A Recommendation for Machine-To-Machine Communication Preparation in the 5G Era - Nurpulaela, Lela; Hadikusuma, Ridwan Satrio (Jurnal ELTIKOM : Jurnal Teknik Elektro, Teknologi Informasi dan Komputer, 2023)
This study aims to provide recommendations regarding frequency and channel settings for machine-to-machine (M2M) communication in preparation for the 5G era in Indonesia. In the rapid development of the Internet of Things (IoT), M2M communication is becoming increasingly important to support efficient and reliable connectivity between IoT devices. In this study, we conduct an in-depth analysis of the available frequency spectrum in Indonesia, considering existing regulatory constraints and technical requirements. The results of this study show that the frequency bands 920-925 MHz and 925-928 MHz suit M2M communication in Indonesia with the suggested channel settings. These recommendations are based on spectrum availability, M2M communication needs, and relevant technical requirements. Implementing these recommendations is expected to increase the efficiency and reliability of M2M communications in Indonesia, facilitate the further development of IoT technology, and prepare Indonesia well to face the 5G era. This study contributes to designing a regulatory framework and optimal spectrum use to support successful M2M communications in Indonesia.